Travel writing for tourism and city branding urban place-writing methodologies - Mansfield, Charlie; Potocnik Topler, Jasna (Routledge, Taylor & Francis Group, 2023)
"Travel Writing for Tourism and City Branding is an insightful, expert-led book which provides tourism students with a practice-based approach to producing researched literary travel writing on an urban destination, using the writing process as a research tool in itself. The book is scientifically supported with full academic references for researchers. This informative and practical volume will be of great interest to students of tourism marketing, destination marketing, place branding, travel writing, as well as current creators of commercial tourism marketing content"--